Evaluation of ZnO-NPs in canned seafood by single particle ICP-MS determination. (20th October 2021) - Copat, C; Grasso, A; Arena, G; Cristaldi, A; Oliveri Conti, G; Ferrante, M
Abstract:  : Zinc is a well-known essential micronutrient, widely used as a food supplement, antimicrobial agent and food preservation. NOAEL was established at 50 mg/person per day and an upper limit of 25 mg/person per day was recommended. ZnONPs are GRAS substances approved by FDA. Nanotechnology is an emerging issue because of the industrial widespread use of ZnO nanoparticles and their potential toxicity and bioaccumulation. Aim of this study is to provide information regarding the quantification of ZnO-NPs, which may be intentionally or unintentionally added, in different brands of canned tuna (CT) and canned clam (CC), and to provide a first esteem of dietary exposure. Canned seafood was subjected to an alkaline digestion with TMAH. Assessment of ZnONPs was performed using a NexION 350D with the Syngistix Nano Application software (Perkin Elmer), allowing to identify number of particles, size and size distribution of metal NPs with the simultaneous quantification of the dissolved elemental concentration. Estimated Meal Intake was evaluated for adults by assuming a meal size of 227 g, 70 years old and 70 Kg of b.w. Results revealed a comparable mean size range between the considered food item (CT 69-80 nm; CC 75-83 nm). Concentration of ZnONPs are significantly higher in CC versus CT (CT 3.2-9.8 µg/Kg; CC 7.7-11.3 µg/Kg). The same we found for dissolved Zn concentration (CT 19.1-28.4 mg/Kg; CC 27.4-39.2 mg/Kg). For CT it was estimated an EMI of 0.018 µg/Kg bw for ZnONPs and 79.9 µg/Kg bw for dissolved Zn. For CC it was estimated an EMI of 0.031 µg/Kg bw for ZnONPs and 109 µg/Kg bw for dissolved Zn. Our findings revealed that ZnO-NPs have the potential to bioaccumulate in marine organisms, and seafood could be an important uptake route of ZnONPs. These results are a first important step to understand the ZnONPs human dietary exposure, but the characterization and quantification of ZnONPs is necessary for a large number of food items. Key messages: The extensive use and discharge of ZnONPs will probably expose human population to concentration higher than the recommended upper limit 25 mg/person per day. The quantification of ZnONPs dietary exposure will be useful for risk assessors in developing provisional tolerable daily intake.